Sociodemographic relationship with the prevalence of caries using ICDAS in children aged 12-16 years : Hubungan sosiodemografi dengan prevalensi karies menggunakan ICDAS pada anak usia 12-16 tahun - Fuad Husain Akbar; Rasmidar Samad; Burhanuddin Daeng Pasiga; Ramlah Wati Arsyad (Makassar Dental Journal PDGI Makassar, 2022)
This study is aimed to determine the relationship between parental occupation, education level, and household income with the prevalence of dental caries inchildren aged 12-16 years. This analytic observational research uses cross sectional study method and samples were determined with purposive sampling. Surveywas conducted in Bantaeng regency with target population were adolescents aged 12-16 years, which amounts to 531, consisted of 233 boys and 298 girls. Sevenchildren with incomplete data were excluded. Data are analysed with Chi-Square test; gets the prevalence of dental caries in children frequently found in girls thanboys and based on sociodemography, there was no significant relationship. It is concluded that there was no significant re-lationship between sociodemographicand dental caries prevalence in children aged 12-16 years in Bantaeng Regency except in the father's and mother's education categories.